Motor and Sensory Changes in Postural Control of Older Adults - Cruz, Caio Ferraz; Barela, José Angelo [UNESP] (Springer Nature, 2024)
Postural control involves a complex relationship between sensory information and muscular activity, with the purpose of postural orientation and postural equilibrium. The aging process leads to several changes in the sensory and motor systems, with consequent deterioration of the postural control functioning. In this chapter, we start from the definition of aging by Spirduso WW, Francis KL, MacRae PG. Physical dimensions of aging. 2nd ed. Champaign: Human Kinetics; 2005, which makes reference to the lack of adaptability, to develop a line of discussion on postural control and aging, analyzing the effects of sensory and motor changes typical of aging on the mechanisms and strategies for controlling the standing posture in older people. Special attention is given to the role of physical activity as a factor in preventing losses in obtaining sensory information and, consequently, deterioration of postural control. Finally, we present sensory reweighting as an adaptation strategy for older people to maintain the functionality of the postural control system and ensure safety in their motor actions. We conclude that the aging process, with regard to postural control, does not necessarily cause a loss of adaptability, but it is a matter of readaptation in older people to their new sensory and motor conditions, which require changes in the sensorimotor relationship to perform with lesser risk to the demands of their daily life tasks.